Mestizaje cultural y relaciones comerciales en la Guajira del siglo XVIII - Lizarazo, Tania (Pontificia Universidad Javeriana, 2014)
This essay presents an overall picture of the acculturation process that proceed "both ways" in the Guajira during the Eighteenth Century as a result of illicit commercial relations maintained between Europeans and natives of the Guajira. This situation createda state of permanent conflict with the Spaniards who were unable to dominate the people of the region. Thus the traditional establishment of the imposition of one culture over another was revised, giving way to the possibility of mutual influence in this coming together of two cultures.